Rotorcraft thickness noise control - Szulc, O. (Archives of Mechanics, 2021)
The paper describes an innovative idea of Thickness Noise Control (TNC) based on adoption of a flow control strategy (i.e. surface ventilation) for acoustic attenuation of helicopter rotor periodic noise. The TNC method is relying on incorporation of multiple cavities (closed by perforated panels and linked to low- and high-pressure reservoirs) located in a symmetrical manner at front and rear portions of the blade tip. The efficiency of the new approach is verified using a two-bladed model rotor of Purcell (untwisted variant of the blade of Bell UH-1H Iroquois helicopter) in low-thrust hover conditions. The results of numerical simulations, obtained with CFD solver (Spalart–Allmaras turbulence and Bohning–Doerffer transpiration models), indicate that in the near-field of the blade tip, both the amplitude and spectral contents of pressure impulses of emitted thickness noise are significantly improved. The TNC method, in the proposed unsteady mode of operation, turns out to be a suitable means of thickness noise reduction in forward flight. Moreover, it is demonstrated that by proper azimuthal activation the efficiency is almost unaltered, while the rotor torque penalty and required transpiration mass-flux are decreased by a factor of 3–5 compared to a steady arrangement.